2015 European Conference on Optical Communication (ECOC) 2015
DOI: 10.1109/ecoc.2015.7341638
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on nonlinear tolerance of subcarrier multiplexed signals with spectrum optimization

Abstract: We numerically and experimentally investigate spectrum optimization techniques including adjustment of subcarrier symbol rate and subcarrier frequency spacing for multi-subcarrier modulation. Improvement of nonlinear tolerance is experimentally evaluated in Nyquist-FDM-DP-QPSK through 2,400 km transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…However, the gain could also be attributed to other beneficial effects of using subcarriers in that particular set-up. Other WDM experiments [9]- [11] found conflicting results, between about 8% MR gain and no gain at all. Overall, at present, experimental evidence appears to be inconclusive as to the extent of possible SRO gains.…”
mentioning
confidence: 93%
“…However, the gain could also be attributed to other beneficial effects of using subcarriers in that particular set-up. Other WDM experiments [9]- [11] found conflicting results, between about 8% MR gain and no gain at all. Overall, at present, experimental evidence appears to be inconclusive as to the extent of possible SRO gains.…”
mentioning
confidence: 93%
“…A 19 × 128 Gb/s PM-QPSK experiment has been reported in [5], where 12% extended reach was found with an 8-subcarrier channel configuration. In [4], enhanced SRO benefits were found by increasing the inter-subcarrier spacing in a 8channel PM-QPSK experiment, yielding 0.7 dB gain in required OSNR after propagation, even suffering from a 0.3 dB back-to-back (B2B) MSC implementation penalty. Indeed, increased MSC B2B penalties relatively to SC transmission have been reported in several recent works.…”
Section: Introductionmentioning
confidence: 99%
“…It exploits the flexibility on signal design provided by fast digital-to-analog converters (DACs), enabling to create multiple electrically-generated subcarrier signals composed of an adjustable number of low symbol-rate tributaries. The main competitive advantage of MSC over standard SC transmission lies on the additional nonlinear robustness provided by the recently identified symbol-rate optimization (SRO) phenomenon [1][2][3][4][5][6][7][8]. Exploring the additional degree of freedom (number of subcarriers) provided by MSC transmission, several analytical, simulation and experimental works have identified that the total nonlinear interference (NLI) impinging on a given channel under test (CUT) turns out to depend on the per-subcarrier symbol-rate [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the gain could also be attributed to other beneficial effects of using subcarriers in that particular set-up. Other WDM experiments [39][40][41] found conflicting results, between about 8% MR gain and no gain at all. One ultra-long-haul experiment 36 based on PM-QPSK recently found a 12.5% reach increase over PSCF, from 12,610 km at 32 Gbaud, to 14,180 km at 4 Gbaud.…”
Section: Impact Of Symbol Rate On System Reachmentioning
confidence: 95%
“…Besides theory and simulation, also various experimental papers have lately addressed SRO. [36][37][38][39][40][41][42][43] The results have not been unanimous. Note in passing that, given the low value of the optimum rates, these experiments were conducted by breaking up each single optical channel into electrical subcarriers, generated digitally through the transmitter DSP and DACs (see Section 5 for a more detailed description of subcarrier multiplexing).…”
Section: Impact Of Symbol Rate On System Reachmentioning
confidence: 99%